Efeito agudo de brincadeiras ativas sobre potenciais neuroel??tricos relacionados ?? fun????o executiva em crian??as - Brito, St??phany Vieira (2017)
Event-related brain potentials (ERPs) have been instrumental for discerning the relationship between physical activity and aspects of cognition in children. We aimed to verify and compare the waveform of N450 ERP component in Stroop task between active play, passive play and control sessions in children. 13 girls and boys (9.5??0.8yr; 32.05??5.9kg; 1.38??0.1m; 16.36??4.2%body fat) participated on this study. Firstly, they were performed anthropometric evaluations. Thereafter, three sessions lasting 30min were performed in randomized order: 1) Control ??? seated watching a documentary (92.4??8.9bpm); 2) Active Play ??? games with movement, eg. jumping jacks, running, jumping (152.8??16.31bpm); 3) Passive Play ??? playing games seated, eg. puzzles of colors, animals and numbers (99.6??28.2bpm). Subsequently, they completed a Stroop task (GO/No-go) while brain electrical activity was recorded with EEG. ERPs were recorded and calculated from electrodes at Fz, F3, F4, Fp1 and Fp2. Mean peak amplitude of N450 component were used to compare the electrical brain responses between sessions. The ANOVA of N450 mean amplitudes revealed a significant main effect for interaction of factor frontal anterior in control sessionF(2,36) = 3.63, p = 0.04 (fig 1). The N450 amplitude in the incongruent condition was less negative in active play than in control session in the frontal sites (p=0.11). In the Stroop test, no significant differences in reaction time between sessions were observed (F (1.92) = 0.05, p = 0.94). The control differed in congruent Go responses between the passive and active sessions (p = 0.01), and the results of the active session also differed from the passive (p = 0.04). The comparison of total errors per session also presented a significant difference (p = 0.02) between control and passive (F (1,71) = 8.8, p <0.05). In conclusion, 30 minutes of active play promoted a lesser response conflict in the incongruent stimuli in the Stroop test, in the N450 component, in addition to a greater activation of the prefrontal cortex.